Modeling Phytoplankton Blooms and Inorganic Carbon Responses to Sea‐Ice Variability in the West Antarctic Peninsula. Issue 4 (28th April 2021) - Schultz, C.; Doney, S. C.; Hauck, J.; Kavanaugh, M. T.; Schofield, O.
Abstract: The ocean coastal‐shelf‐slope ecosystem west of the Antarctic Peninsula (WAP) is a biologically productive region that could potentially act as a large sink of atmospheric carbon dioxide. The duration of the sea‐ice season in the WAP shows large interannual variability. However, quantifying the mechanisms by which sea ice impacts biological productivity and surface dissolved inorganic carbon (DIC) remains a challenge due to the lack of data early in the phytoplankton growth season. In this study, we implemented a circulation, sea‐ice, and biogeochemistry model (MITgcm‐REcoM2) to study the effect of sea ice on phytoplankton blooms and surface DIC. Results were compared with satellite sea‐ice and ocean color, and research ship surveys from the Palmer Long‐Term Ecological Research (LTER) program. The simulations suggest that the annual sea‐ice cycle has an important role in the seasonal DIC drawdown. In years of early sea‐ice retreat, there is a longer growth season leading to larger seasonally integrated net primary production (NPP). Part of the biological uptake of DIC by phytoplankton, however, is counteracted by increased oceanic uptake of atmospheric CO2 . Despite lower seasonal NPP, years of late sea‐ice retreat show larger DIC drawdown, attributed to lower air‐sea CO2 fluxes and increased dilution by sea‐ice melt. The role of dissolved iron and iron limitation on WAP phytoplankton also remains a challenge due to the lack of data. The model results suggest sediments and glacial meltwater are the main sources in the coastal and shelf regions, with sediments being more influential in the northern coast. Plain Language Summary: Some coastal ocean areas of Antarctica, like the West Antarctic Peninsula (WAP), have high biological productivity, which indicates they could absorb more atmospheric CO2 . Studying these regions is hard since weather, clouds and sea ice make satellite and cruise data collection challenging. Using models is an alternative to fill in the gaps in the data. In this study, we used an ocean model that simulates circulation, sea ice, biological productivity, and the nutrient cycle in the WAP to study how much sea ice and biology influence the carbon cycle. We find that in years when the ice season is long there is a smaller flux of carbon between ocean and atmosphere, and more dilution of the surface waters by sea ice melt. Although the amount of inorganic carbon in the surface ocean is low by the end of the productive season, this does not reflect more CO2 being taken up or more biological productivity. In years of shorter sea ice season, in contrast, the ocean takes up more atmospheric CO2 and has a longer productive season. This is because the surface ocean is exposed for longer, so gas transfer happens more easily and there is more light available for photosynthesis. Key Points: Longer growth season in years of early sea‐ice retreat show higher seasonally integrated NPP, despite lower chlorophyll in January Sea ice is important for DIC drawdown as it influences the duration of phytoplankton bloom, air‐sea CO2 fluxes, and dilution by meltwater In the WAP, sedimentary iron has a larger role in the northern coast and shelf, glacial meltwater likely the main source in the south